Meta Analisis Pengaruh Model Pembelajaran Kooperatif Terhadap Hasil Belajar Siswa Pada Pembelajaran Fisika - Fitrie Muliani; Abdul Salam; Dewi Dewantara (Indonesian Publication Center, 2022)
This meta-analysis aims to evaluate the effectiveness of the cooperative learning model on students' physics learning outcomes through a systematic synthesis of 29 primary studies (2012–2021). The research focuses on analyzing the effect size across overall data, educational levels, learning topics, types of learning outcomes, and variations of the cooperative model. The findings indicate that, overall, the cooperative learning model is highly effective in enhancing physics learning outcomes, with a mean effect size of 1.124 (categorized as a large effect). This result is consistent across all educational levels (from junior high to senior high/vocational schools), all 13 learning topics analyzed, the three types of learning outcomes, and all variations of the cooperative model utilized. Consequently, the cooperative learning model is proven to be a robust instructional strategy that exerts a significant positive impact on students' physics academic achievement.